Dodeca-Helix: Pentingnya Mengintegrasikan 12 Dimensi Pemangku Kepentingan untuk Menumbuhkan Ekosistem Inovasi di Kota Baubau - Saksono, Herie (Kainawa: Jurnal Pembangunan dan Budaya, 2024)
The evolution of innovation models in regional development has progressed from Triple-Helix to more complex models, yet gaps remain in accommodating the roles of various stakeholders in regional innovation ecosystems. This research examines how the Dodeca-Helix model can integrate 12 stakeholder dimensions to foster innovation ecosystem in Baubau City. Through a qualitative approach with descriptive analysis method, the research was conducted in four stages: literature study, stakeholder mapping, conceptual framework development, and empirical validation. Data collection was carried out through document analysis and regulations related to regional innovation. The results show that the implementation of the Dodeca-Helix model contributed to the improvement of Baubau City's status from "Less Innovative" to "Innovative" during the 2023-2024 period. This model proved effective in orchestrating specific roles of 12 stakeholder dimensions, from academics to ultimate beneficiaries. These findings confirm that successful regional innovation requires active involvement from various stakeholders beyond conventional helix models. The research recommends developing more effective coordination mechanisms, measurable monitoring and evaluation systems, and strengthening institutional capacity for long-term collaboration sustainability.